Understanding and safeguarding patient dignity in intensive care - Nyholm, Linda (Nursing ethics, 2017)
Background:Dignity has been highlighted in previous research as one of the most important ethical concerns in nursing care. According to Eriksson, dignified caring is related to treating the patient as a unique human being and respecting human value. Intensive care unit patients are vulnerable to threatened dignity, and maintaining dignity may be challenging as a consequence of critical illness.Objectives:The aim is to highlight how nurses in an intensive care setting understand patient dignity, what threatens patient dignity and how nurses can safeguard patient dignity.Research design and participants:Data materials were collected through a survey questionnaire which contained open questions about patient dignity, and the text was analysed using hermeneutic reading and text interpretation. Totally, 25 nurses employed in an intensive care unit in Finland participated in the study.Ethical considerations:The study follows the guidelines for good scientific practice by the Finnish Advisory Board on Research Integrity and the ethical principles according to the Declaration of Helsinki.Findings:Findings revealed that nurses recognize the patients’ absolute dignity by regarding them as unique human beings. The nurses also recognize the importance of shared humanity in preserving patient dignity. Intensive care patients’ dignity is threatened by negative attitudes and when their integrity is not being protected. Dignity is also threatened when patients and nurses are not part of the patients’ care and patient care decisions, when patients receive care against their will and because of the acute nature of intensive care.